Efek Kebakaran Hutan Kalimantan Pada Hukum Internasional - Andhika Ivan Putra Pamungkas; Felixs Ade Santoso; Deaz Aji Pratama; Mohammad Arya Dharmaputra; Janter Panjaitan; Syahputraaditya Kusrin Surbakti; Rani Pajrin (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
Indonesia is an archipelagic country where almost more than half of its area has forests that store various kinds of plants, it indicates that almost all regions of Indonesia have a forest ecosystem that are very important for the survival of Indonesia and the world. Forests have many positive impacts that can be used by the community to become a livelihood. Behind the forests owned by Indonesia, there are various problems that are of international concern, one of which is forest fires. The causes of forest fires are very diverse which causes the impact of smoke from forest fires to spread to our neighboring countries such as Singapore and Malaysia which makes smoke from these forest fires a negative view of the international world on Indonesia. Human resource factors are important in the prevention and handling of forest fires, human factors such as opposing loads are positive and negative, on the one hand humans can prevent forest fires on the other hand humans can be the cause of forest fires. These things are complications experienced by Indonesia in handling and preventing forest fires, however, natural factors can also affect the occurrence of forest fires. The country has a responsibility in maintaining its natural sustainability as well as the country has a responsibility in the smoke problem that causes neighboring countries to suffer losses from both the economic sector and other sectors.